2017
DOI: 10.1155/2017/1645074
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotype Distribution among Cervical Cancer Patients prior to Brazilian National HPV Immunization Program

Abstract: To evaluate the impact of HPV immunization and possible changes in virus type-specific prevalence associated with cervical cancer, it is important to obtain baseline information based on socioeconomic, educational, and environmental characteristics in human populations. We describe these characteristics and the type-specific HPV distribution in 1,183 women diagnosed with cervical cancer in two Brazilian healthcare institutions located at the Southeastern (Rio de Janeiro/RJ) and the Amazonian (Belém/PA) regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
2
13
0
3
Order By: Relevance
“…Similarly, a study conducted in Heidelberg, Germany, identified HPV types 6 and 11 as the most frequent genotypes in their study of mammary lesions and invasive breast carcinomas 3 . In a similar way, a study conducted in Rio de Janeiro with cervical cancer patients 25 have found low-risk types in tumour samples. Another study also indicated that women who develop viral warts are at a significantly higher risk of developing BC 26 ; low-risk HPV types are causal agents of genital warts 3 , 7 .…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, a study conducted in Heidelberg, Germany, identified HPV types 6 and 11 as the most frequent genotypes in their study of mammary lesions and invasive breast carcinomas 3 . In a similar way, a study conducted in Rio de Janeiro with cervical cancer patients 25 have found low-risk types in tumour samples. Another study also indicated that women who develop viral warts are at a significantly higher risk of developing BC 26 ; low-risk HPV types are causal agents of genital warts 3 , 7 .…”
Section: Discussionmentioning
confidence: 61%
“…The prevalence of HPV73 in cervix cancer varies by DNA testing method and geographic region, for example, 0.5% worldwide to 1.4% in Rio de Janeiro, Brazil . HPV73 has also been detected in 11% of adenosquamous cancers, and a recent report found HPV73 DNA in three out of 10 cervical SCCs that were negative by Hybrid Capture 2 testing .…”
Section: Discussionmentioning
confidence: 99%
“…Between June 2011 and March 2014, 590 patients were referred to the National Cancer Institute (INCA, Instituto Nacional de Cancer ), Rio de Janeiro, Brazil, for treatment of CxCa. A total of eight (1.4%) women had HPV73‐positive CxCa specimens detected by PCR and Sanger sequencing as previously reported and were designated SA162–SA169 . All subjects gave informed consent and completed an epidemiological questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study material consisted of 137 CC samples selected from a previously reported pool of 590 biopsies of invasive cervical cancer [27] , 70 associated with HPV16, 37 with HPV18 and 30 with HPV45. Samples were collected at diagnosis from patients treated at the Instituto Nacional de Câncer (INCA - Rio de Janeiro, Brazil) referred for treatment between June 2011 and March 2014.…”
Section: Methodsmentioning
confidence: 99%